IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY IN PT. TIMAH (PERSERO) TBK, - Khalistia Andina Paripurna; Gugus Irianto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aimed to describe the practice of implementation of Corporate Social Responsibility at PT. Timah (Persero) Tbk. This research is a qualitative descriptive study analysing a case in a company (single case study). Secondary data from the company's annual report documents used in this study. The results showed that, PT. Timah implement social responsibility in three aspects, each of the environmental, social, and economic. For the environmental aspects, the company implemented an environmental monitoring program, and environmental management programs. In the social aspect provide educational facilities, health facilities, and religious facilities. In the aspect of welfare is to support the social life include support for: public facilities and infrastructure, improvement of social welfare and disaster relief. For the economy, companies implement a partnership program in the form of loans (revolving fund). Keywords: Corporate Social Responsibility, PT. Timah, Tbk., enviromental, social, welfare, economy.